RELATIONSHIP BETWEEN PHYSICAL ACTIVITY AND DEPRESSION IN ELDERLY: AN INTEGRATING REVIEW - Mendes, Gabriel Augusto Bernardes; Carvalho, Maria Virgínia de; Silva, Antonio Márcio Teodoro Cordeiro; Almeida, Rogério José de (Journal of Health Care, 2017)
Introduction: Scientific evidence has shown that population ageing is a reality. The elderly is becoming healthier, productive and practicing physical activity. However, one of the most striking injuries in this population is depression. Objective: This article aims to analyze in a biopsychosocial perspective the relationship between the practice of physical activity and depression in the elderly. Method: This is an integrative review of the scientific literature concerning the relationship between physical activity and depression in the elderly. For the selection of scientific articles, the databases Virtual Health Library, Capes Periodicals and PubMed were consulted. Results: Three categories of the phenomenon emerged and were analyzed: relationship between physical activity and depression in the elderly, biological factors of physical activity and depression in the elderly and group physical activity and depression in the elderly. Conclusion: Evidence has been found that the regular practice of physical activity can improve physical conditioning, hormonal regulation and is an effective alternative for social group living. It is concluded that regular physical exercise in the elderly plays a fundamental role in the prevention and reduction of depressive symptoms.